The effect of OK-432 (Picibanil) injection on the histopathology of nasal turbinate - Sengul, S.; Kaygusuz, I.; Akin, M. M.; Yalcin, S.; Karlidag, T.; Keles, E.; Arslan, I. (Cambridge Univ Press, 2015)
Objective: This study aimed to assess the histopathological effect of OK-432 (Picibanil) on rabbit nasal turbinates. Methods: A total of 21 rabbits were divided into 3 treatment groups and various parts of both nasal turbinates were injected with 0.5 ml OK-432, 0.2 ml OK-432 or 0.6 ml saline (control). Bilateral nasal turbinates were later excised and studied under light microscopy to assess any histopathological changes. Results: Animals in the 0.2 ml and 0.5 ml OK-432 groups exhibited mild ciliary loss, goblet cell loss and epithelial damage, and a marked increase in inflammatory cell infiltration, submucosal vascularisation and fibrosis. There was a significant difference in histopathological changes between the two OK-432 treated groups. In addition, each OK-432 treated group had significantly more inflammatory cell infiltration, increased submucosal vascularisation and fibrosis compared with controls. Conclusion: The marked fibrosis observed in OK-432-injected turbinates may be responsible for a reduction in turbinate size.
Keywords: Turbinates; Hypertrophy; Nasal Obstruction; Picibanil